Risk Factors Associated With Abnormal Urinalysis in Children - Zhong, Xuhui; Ding, Jie; Wang, Zheng; Gao, Yan; Wu, Yubin; Shen, Ying; Song, Hongmei; Zhao, Zhengyan; Chen, Xinxin; Zhang, Puhong; Xu, Guobin; Yao, Chen; et al. (Frontiers in Pediatrics, 2021)
Background Targeted urinalysis has been suggested to improve screening efficiency in adults. However, there is no well-defined target population in children yet, with limited information on the risk factors for urinalysis abnormalities. Methods Children from infants to 17 years old were randomly selected. Dipstick urinalysis was initially performed. Among those who were abnormal, a repeat dipstick or dipstick with microscopic urinalysis was performed for confirmation. Results In total, 70,822 children were included, with 37,866 boys and 32,956 girls. Prevalence of abnormal urinalysis was 4.3%. Age was significantly associated with abnormal urinalysis, with the highest prevalence among 12- to 14-year-olds. Girls were 2.0 times more likely to exhibit abnormalities. Compared with children whose guardians had a college degree or higher, those whose guardians had a high school degree or lower had a higher likelihood of abnormalities. Geographic location was also associated with abnormal results. Conclusion Girls, children aged 4, 12 to 14 years old, and children whose guardians had a low educational level and children in certain geographic locations were significantly associated with abnormal urinalysis. Identification of children at high risk would contribute to targeted urinalysis screening.